2020
DOI: 10.4301/s1807-1775202017009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors that Have Impact On Consumers’ Trust in Mobile Payment Systems in Australia

Abstract: Trust plays a vital role in the adoption of a new payment system in so far as people need to trust that the prevailing currency, or in other words, money, is recognized by all stakeholders. With the evolution of the payment methods, shifting from paper-based to electronic-based, building consumer trust has become a vital element for the success of businesses involved in the mobile payment systems sector. In this context, the aim of this study was to delve deeper into the factors that have impact on consumers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
0
10
1
Order By: Relevance
“…Changes in the value of R-Square can be used to explain whether certain latent variables on the dependent variable have a substantive effect. R-Square values of 0.75, 0.50, and 0.25 can be concluded that the model is strong, moderate, and weak [28,30]. The summary of the evaluation criteria for the structural model can be seen in Table 3.…”
Section: Structural Equation Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…Changes in the value of R-Square can be used to explain whether certain latent variables on the dependent variable have a substantive effect. R-Square values of 0.75, 0.50, and 0.25 can be concluded that the model is strong, moderate, and weak [28,30]. The summary of the evaluation criteria for the structural model can be seen in Table 3.…”
Section: Structural Equation Modelingmentioning
confidence: 99%
“…The software used is Smart PLS 3.0. In general, two main stages must be carried out in testing the SEM method, namely: evaluation of the measurement model and evaluation of the structural model [28,30].…”
Section: Structural Equation Modelingmentioning
confidence: 99%
See 3 more Smart Citations